Synthetic Artificial Long Non-coding RNA Shows Higher Efficiency in Specific Malignant Phenotype Inhibition Compared to the CRISPR/Cas Systems - Yao, Lin; Zhang, Quan; Li, Aolin; Ma, Binglei; Zhang, Zhenan; Liu, Jun; Liang, Lei; Zhu, Shiyu; Gan, Ying; Zhang, Qian (Frontiers in Molecular Biosciences, 2020)
Objective： Both oncogenic transcription factors (TFs) and microRNAs (miRNAs) play an important regulator in human cancer by transcriptional and post-transcriptional regulation, respectively. These phenomena raise questions about the ability of artificial device to regulate miRNAs and TFs simultaneously. In this study, we aimed to construct an artificial long non-coding RNA, “alncRNA”, which imitated CRISPR/Cas systems and to illuminate its therapeutic effects in bladder cancer cell lines. At the same time, we also compared the efficiency of alncRNA and CRISPR/Cas systems in regulating gene expression. Study design and Methods: Base on engineering principles of synthetic biology, we combined tandem arrayed cDNA sequences of aptamer for TFs with tandem arrayed cDNA copies of binding sites for the miRNAs to construct alncRNA. In order to prove the utility of this platform, we chose β -catenin，NF-κB ， miR- 940 and miR-495 as the functional targets and used the bladder cancer cell lines 5637 and T24 as the test models. Real-time Quantitative PCR (qPCR), dual-luciferase assay and relative phenotypic experiments were applied to severally test the expression of relative gene and therapeutic effects of our devices. Result Dual-luciferase assay indicated alncRNA could inhibit transcriptional activity of TFs. What’s more, the result of qPCR showed that expression levels of the relative TFs target genes and miRNAs were reduced by corresponding alncRNA and the inhibitory effect was better than CRIPSR dCas9-KRAB. By functional experiments, decreased cell proliferation, increased apoptosis, and motility inhibition were observed in alncRNA-infected bladder cells. Conclusion In summary, our synthetic devices indeed function as anti-tumor regulator, which synchronously accomplish transcriptional and post-transcriptional regulation in bladder cancer cell and show higher efficiency in specific malignant phenotype inhibition compared to the CRISPR/Cas systems. Most importantly, Anti-cancer effects were induced by the synthetic alncRNA in the bladder cancer lines. Our devices, therefore, provides a novel strategy for cancer therapy and could be a useful “weapon” for cancer cell.